2022
DOI: 10.1186/s40001-022-00756-2
|View full text |Cite
|
Sign up to set email alerts
|

Unusually high incidence of polyomavirus JC infection in the higher grade of colorectal cancer tissues in Taiwan

Abstract: Introduction The human JC polyomavirus (JCPyV) has been detected in colorectal cancer (CRC) tissues and is suggested to contribute to CRC tumorigenesis. The rearrangement of the JCPyV regulatory region is supposedly associated with CRC development. The progression of CRC involves the stepwise accumulation of mutations. The large tumor antigen (LT) of JCPyV can trigger uncontrolled cell cycle progression by targeting oncogenes, and tumor suppressor genes, and causing chromosome instability. Few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…It is widely recognized that certain oncogenic viruses have the potential to contribute to the development of human cancers. Among these viruses, human papillomavirus (HPVs) and the four human polyomaviruses (SV40, BKPyV, JCPyV, and MCPyV) have been firmly established as being linked to human tumor formation [ 6 11 ]. However, the existing literature on the role of these viruses in the onset or progression of colon cancer is limited and contentious [ 8 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely recognized that certain oncogenic viruses have the potential to contribute to the development of human cancers. Among these viruses, human papillomavirus (HPVs) and the four human polyomaviruses (SV40, BKPyV, JCPyV, and MCPyV) have been firmly established as being linked to human tumor formation [ 6 11 ]. However, the existing literature on the role of these viruses in the onset or progression of colon cancer is limited and contentious [ 8 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Samples that tested positive for HPVs underwent genotyping using the QIAGEN PCR kit, following the methodology outlined by Nishiwaki et al [ 11 ]. The DNA amplification process involved an initial denaturation step at 95°C for 15 minutes, followed by 40 cycles of denaturation at 94°C for 30 seconds, annealing at 65°C for 90 seconds, and extension at 72°C for 90 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, another study, which examined JCPyV seropositivity rates in multiple sclerosis (MS) patients during COVID-19, discovered that conversion rates declined during lock down [ 74 ]. Other studies have found an increasing prevalence of JCPyV LTAg in colorectal cancers [ 75 , 76 , 77 , 78 , 79 ]. Our laboratory has demonstrated that MuPyV can cause systemic infection after oral gavage inoculation (AE Lukacher, unpublished observations).…”
Section: How Is Jcpyv Transmitted?mentioning
confidence: 95%